Pengaruh Likuiditas, Solvabilitas, dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Sektor Energi Yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2021-2024 - Novia Dwi Prasinta; Subarjo Subarjo (CV. Rayyan Dwi Bharata, 2025)
This study aims to determine the effect of Liquidity, Solvency, and Profitability on firm value in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. This study used quantitative methods with secondary data obtained from annual financial reports. The research sample consisted of 10 companies selected through purposive sampling and observed over four years, resulting in 40 data observations. The data were analyzed using multiple linear regression and met the classical assumption test. The results show that 1) Liquidity has a positive and significant effect on firm value, 2) Solvency has a positive and significant effect on firm value, 3) Profitability also has a positive and significant effect on firm value, and 4) Liquidity, solvency, and profitability simultaneously have a significant effect on firm value. These findings indicate that companies with strong liquidity, a healthy solvency structure, and high profitability tend to have better firm value. Practically, these financial ratios can be used as indicators in assessing financial performance and the potential for increasing company value in the energy sector.